Water and identity:: an urban case study for densification along Los Angeles River’s Rio Hondo Confluence - Vaglio, Jeffrey C. (ARCC Conference Repository, 2018)
When Los Angeles was founded in 1781, the mountains, river and shore formed the landscape. Today, street grids and a superimposed network of meandering freeways blanket the valleys while clusters of high-rises emerge periodically to provide underpinnings of the city’s identifiable neighborhoods. Only the Los Angeles River is invisible, reduced to concrete-lined drainage channels, denuded of riparian vegetation, bounded by rail lines, hidden behind industrial plants and beneath freeways. What is a river without water? Throughout landscapes, urban and rural alike, rivers and infrastructure intertwine like tendons to connect cities to natural resources and each other. This dance is particularly evident in an 11-mile stretch of the 51-mile river referred to as Reach 2 where the 710 Long Beach Freeway parallels, elevates, and hurdles the concrete-lined depression of the barren riverbed. Ten cities comprise Reach 2, which fail to garner the attention of Downtown Los Angeles to the north and the Long Beach estuary to the south. As a result of this intermittency, these cities suffer from social and infrastructural neglect, while struggling to develop positive community identity. In modern multi-city metropolitan areas, governmental centers dominate the political infrastructure. Meanwhile, physical infrastructures, such as freeways, often divide these cities. This research seeks to invert these paradigms in an effort to celebrate city identity at political borders, and transform physical divisions into cultural connections. Research and a design prototype were developed in a unique multi-disciplinary graduate studio environment. Reach 2 is compared to Tokyo to extract potential community identities to support dense and vibrant future development. Additionally, an innovative four-dimensional land-use analysis is conducted across the region to identify voids/opportunities for optimal multi-use development. These investigations culminate in a design prototype at the Rio Hondo Confluence.